Diffusion‐weighted J‐resolved spectroscopy. Issue 4 (31st October 2016) - Landheer, Karl; Schulte, Rolf; Geraghty, Ben; Hanstock, Christopher; Chen, Albert P.; Cunningham, Charles H.; Graham, Simon J.
Abstract : Purpose: To develop a novel diffusion‐weighted magnetic resonance spectroscopy (DW‐MRS) technique in conjunction with J‐resolved spatially localized spectroscopy (JPRESS) to measure the apparent diffusion coefficients (ADCs) of brain metabolites beyond N ‐acetylaspartic acid (NAA), creatine (Cr), and choline (Cho) at 3T. This technique will be useful to probe tissue microstructures in vivo, as the various metabolites have different physiological characteristics. Methods: Two JPRESS spectra were collected (high b‐value and low b‐value), and the ADCs of 16 different metabolites were estimated. Two analysis pipelines were developed: 1) a 2D pipeline that uses ProFit software to extract ADCs from metabolites not typically accessible at 3T and 2) a 1D pipeline that uses TARQUIN software to extract the metabolite concentrations from each line in the 2D dataset, allowing for scaling as well as validation. Results: The ADCs of 16 different metabolites were estimated from within six subjects in parietal white matter. There was excellent agreement between the results obtained from the 1D and 2D pipelines for NAA, Cr, and Cho. Conclusion: The proposed technique provided consistent estimates for the ADCs of NAA, Cr, Cho, glutamate + glutamine, and myo‐inositol in all subjects and additionally glutathione and scyllo‐inositol in all but one subject. Magn Reson Med 78:1235–1245, 2017. © 2016 International Society for Magnetic Resonance in Medicine.